C10 IN–HOSPITAL MANAGEMENT AND OUTCOMES OF ELECTRICAL STORM: SINGLE CENTER RETROSPECTIVE STUDY. (18th May 2022) - Di Fusco, S; Pignalberi, C; Spinelli, A; Matteucci, A; Aquilani, S; Pandozi, C; Imperoli, G; Colivicchi, F
Abstract: Background: Electrical storm (ES) is a condition characterized by the recurrence of malignant ventricular arrhythmia and is associated with significant morbidity and mortality. The aim of this study was to report the pharmacological and non–pharmacological interventions used to treat ES during hospitalization in an arrhythmia reference center. Methods: We reviewed the medical record of patients consecutively admitted for ES in the intensive care unit of our center over a period of 6 years. Data on diagnostic tests and therapies used during hospitalization to manage these patients were retrospectively collected. Results: Over the study period, 85 patients ((86% male, mean age 74±10 years) were admitted to the intensive care unit of our center for ES. Patient clinical, electrocardiographic, echocardiographic, and laboratory characteristics at hospitalization are reported in Table 1. Twenty–five patients had electrolytic disorders that required intravenous infusion of potassium and/or magnesium. Most patients (53%) were treated with at least one antiarrhythmic drug administered intravenously (Table 2). The most commonly used antiarrhythmic drug was amiodarone (38%). Twenty patients (24%) required more than one antiarrhythmic drug administered intravenously. Twenty–four patients (28%) underwent coronary angiography and seven patients (8%) required percutaneous coronary intervention (PCI). Twenty patients (24%) were treated with catheter ablation of the ventricular tachycardia during the index hospitalization, none of these also required PCI during the hospitalization. Six patients (7%) died during hospitalization after 9±10 days from ES onset, their mean left ventricle ejection fraction was 28% and none of them underwent ablation or PCI during the index hospitalization. Conclusion: ES management in a reference center involves a comprehensive approach that includes multiple pharmacological and non–pharmacological interventions. Furthermore, our study confirms the severe prognosis associated with hospitalization due to ES.